2015
DOI: 10.1038/srep17447
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival fibrosis and the innate barriers to Chlamydia trachomatis intracellular infection: a genome wide association study

Abstract: Chlamydia trachomatis causes both trachoma and sexually transmitted infections. These diseases have similar pathology and potentially similar genetic predisposing factors. We aimed to identify polymorphisms and pathways associated with pathological sequelae of ocular Chlamydia trachomatis infections in The Gambia. We report a discovery phase genome-wide association study (GWAS) of scarring trachoma (1090 cases, 1531 controls) that identified 27 SNPs with strong, but not genome-wide significant, association wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 59 publications
1
27
0
Order By: Relevance
“…The reason for its upregulation alongside IL23A in scarring progressors in response to C. trachomatis relative to expression in nonprogressors is unclear. A genome-wide association study of scarring trachoma suggested that host cell cycle, cell surface receptor signaling, and immune response pathways were associated with scarring, although no specific cytokine risk loci were identified (40).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for its upregulation alongside IL23A in scarring progressors in response to C. trachomatis relative to expression in nonprogressors is unclear. A genome-wide association study of scarring trachoma suggested that host cell cycle, cell surface receptor signaling, and immune response pathways were associated with scarring, although no specific cytokine risk loci were identified (40).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst we are confident that the positive signals from the PRKG1 and NPSR1-AS1 region are interesting enough to warrant further study, we recognize that the false negative rate is very high. To leverage additional power from the small sample, we focused on pathways-wide analysis that was similar to the one used previously [14]. We determined that the ALIGATOR method was somewhat unstable with regards to the specific pathways that were highlighted at different thresholds of nominal significance (Supplementary Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Imputation was carried out as described previously [21,22] and included prephasing with Shapeit [23,24] (informed by HapMap Phase II, build 37) and post-imputation filtering for high quality imputed SNPs with IMPUTE2 info score > 0.8 and/or MAF > 0.01 [14,25]. Imputation was performed with IMPUTE2 [21,22] using the worldwide 1000 Genomes phase I data set of 1092 reference specimens [26].…”
Section: Imputationmentioning
confidence: 99%
See 2 more Smart Citations